Indigenous resistance to German rule in the Pacific colonies of Samoa, Ponape and New Guinea, 1884 to 1914 - Hempenstall, P (1974)
﻿ This study of resistance in the Pacific Islands is an attempt to achieve both a wider and deeper understanding of colonization as it impinged on the Pacific peoples and as it was perceived by their German rulers. The thesis is by no means another imperial history. The major focus is on the Pacific Islander himself, the processes of change in local socirty under the impact of European expansion and a western cash economy, and on the way the colonial relationship functioned at the level of the individual island administration. It emphasizes the power and ability of the Pacific Islanders to make their own adjustments - of interest and ideology - to the new culture and its demands and does so through the comparison of three cultural regions within the one historical dimension, a method which Pacific historians have barely exploited at all. It represents the first intensive history of German Ponape in particular, using original documentation, while it opens up totally unexplored areas of that 'forgotten imperialism' which was such a critical phase in the modern histories of the new states of Samoa and New Guinea. The thesis is divided into two parts. Part One consists of three 'case studies' of colonial contact and interaction. In each case the pre-German period has been examined for a broader historical background. The modes of adaptation achieved in this earlier period largely determined the pattern of Pacific Island response under German rule. For more than two decades before 1900, Europeans and Samoans had been engaged in a constantly fluctuating struggle for the right to control the group's economic and political destiny. The Samoan district factions often encouraged this conflict in an effort to have their various candidates recognized as the paramount chief of the Samoan Islands, but they were also capable of offering solid opposition when Europeans interfered in their political affairs above certain limits. The history of Samoan response to German rule after 1899 details the struggle between the older chiefly elites and the Governor, tfilhelm Solf. The chiefs, under the orator Lauaki, campaigned shrewdly to have their traditional political authority and prerogatives institutionalized as part of the German system of colonial rule. Though Golf, whose objectives were diametrically opposed to the traditional political dynamics of the group, was at first forced to compromise with the chiefs, he thwarted their campaign in the end by exploiting inherent weaknesses in the political structure and relying on his growing paternal authority with the mass of the people. [Please see pdf. for full abstract.]